Two new species of deep-water xanthid crabs of the genera Euryxanthops Garth & Kim, 1983, and Medaeops Guinot, 1967 (Crustacea: Decapoda: Brachyura: Xanthidae) from New Zealand - Ng, P.K.L. (2014)
Zootaxa